A composite polymer electrolyte containing magnetic hollow nanorods and its preparation method and application

By introducing magnetic hollow nanorods into the composite polymer electrolyte of lithium-ion batteries and oriented them vertically using magnetic fields, the problem of uncontrollable growth of lithium dendrites is solved, and the electrochemical performance and safety of the battery are improved.

CN117438645BActive Publication Date: 2025-03-25JIANGXI NORMAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311593065.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-27
Publication Date
2025-03-25
Estimated Expiration
2043-11-27

AI Technical Summary

Technical Problem

The composite polymer electrolytes of existing lithium-ion batteries have problems with uncontrollable growth of lithium dendrites on the lithium metal negative electrode, resulting in the actual specific capacity of the battery being lower than the theoretical value and poses safety hazards.

Method used

Using a composite polymer electrolyte containing magnetic hollow nanorods, a magnetic Fe3O4 core is introduced when synthesising nanorods and a magnetic field is applied during the preparation of the electrolyte, the nanorods form a vertically oriented ion transport channel to promote uniform deposition of lithium ions.

Benefits of technology

It significantly improves the ionic conductivity and interface stability of lithium-ion batteries, reduces the generation of lithium dendrites, and improves the safety performance and cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117438645B_ABST
    Figure CN117438645B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of polymer electrolyte preparation, and discloses a composite polymer electrolyte containing magnetic hollow nanorods, a preparation method and application thereof. The composite polymer electrolyte prepared by the present invention comprises magnetic hollow nanorods, a high molecular polymer matrix and a liquid electrolyte. The nanorods are fixed by applying a vertical magnetic field and initiating PEGDA polymerization by ultraviolet light, and the added PVDF can ensure the mechanical properties of the composite polymer electrolyte. Orderly arranged nanorods can form vertical lithium ion transmission channels, overcoming the problem of increased lithium ion conduction distance due to irregular distribution of nanofillers, thereby obtaining higher ion conductivity, and can also provide more ion transmission channels, which can promote the uniform distribution of lithium ions on the surface of lithium metal during lithium deposition, and improve the interface performance of lithium metal batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer electrolyte preparation, and in particular relates to a composite polymer electrolyte containing magnetic hollow nanorods and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries (LIBs) have been rapidly developed due to their high operating voltage and long cycle life and are widely used in portable electronic products and electric vehicles. However, the theoretical specific capacity of conventional lithium-ion batteries is limited, making it difficult to meet the growing demand. Lithium metal has the highest theoretical specific capacity (3860 mAh g -1 ) and the lowest redox potential (-3.04 V, relative to standard hydrogen electrode), it is regarded as an ideal negative electrode material for the next generation of batteries. However, the practical application of lithium metal anodes is limited by the uncontrollable growth of lithium dendrites, which is mainly because the active lithium metal electrolyte reacts with the liquid electrolyte to form a brittle and unstable solid electrolyte interface layer (SEI), inducing the formation of lithium dendrites. Solid polymer electrolytes have attracted widespread attention due to their good thermal stability and processability, and can improve the safety performance of lithium batteries. Although solid polymer electrolytes have many advantages, their low room temperature ionic conductivity and poor interfacial compatibility with lithium metal limit their practical application in the field of lithium-ion batteries. Gel polymer electrolytes are composed of a polymer matrix and a liquid electrolyte. They have the advantages of both the plasticity of solid polymer electrolytes and the high ionic conductivity of liquid electrolytes. They can also effectively prevent electrolyte leakage and improve the safety of lithium batteries.

[0003] However, the mechanical strength of gel electrolytes is low, and the lithium metal batteries assembled therein are prone to a series of safety issues such as short circuits and even combustion during operation. Adding inorganic fillers to the polymer matrix and combining the advantages of organic and inorganic electrolytes can effectively improve the mechanical strength of the electrolyte. At the same time, the interface between the filler and the polymer matrix can provide a transmission channel for ion conduction. Compared with spherical nanofillers, one-dimensional linear nanomaterials have a larger specific surface area and can construct an effective transmission channel for the diffusion of lithium ions in the electrolyte. However, in general, one-dimensional nanowires and polymer matrices are simply blended to form a composite, and the nanowires are randomly distributed in the polymer matrix, which increases the transmission distance of lithium ions and thus reduces the electrochemical performance of the composite polymer electrolyte. In addition, the irregularly distributed nanofillers lead to uneven deposition of ions during lithium ion deposition, which in turn affects the interfacial stability between the electrolyte and the lithium metal anode. Therefore, the key to achieving high-performance composite polymer electrolytes is to promote the orderly distribution of nanofillers through reasonable and effective methods. Summary of the invention

[0004] The purpose of the present invention is to solve the deficiencies of the prior art and provide a composite polymer electrolyte containing magnetic hollow nanorods and a preparation method and application thereof, specifically adopting the following technical solutions:

[0005] According to a first aspect of the present invention, a composite polymer electrolyte containing magnetic hollow nanorods is provided, wherein the composite polymer electrolyte comprises magnetic hollow nanorods, a polymer matrix and a liquid electrolyte; the magnetic hollow nanorods are SiO 2 Coated magnetic Fe 3 O 4 of nanofillers.

[0006] The composite polymer electrolyte containing magnetic hollow nanorods prepared by the present invention is composed of magnetic hollow nanorods, a high molecular polymer matrix and a liquid electrolyte. The magnetic hollow nanorods play an important role in the mechanical strength and electrochemical properties of the composite polymer electrolyte. On the one hand, when synthesizing the nanorods, the magnetic Fe 3 O 4 The core is introduced into the filler. Applying a magnetic field to the electrolyte during the preparation of the polymer electrolyte can induce the nanorods to form vertically oriented ion transmission channels, overcoming the problem of increased lithium ion conduction distance due to irregular distribution of nanofillers, thereby obtaining higher ion conductivity; on the other hand, during the lithium deposition process, the orderly distributed ion transmission channels can promote the uniform distribution of lithium ions on the surface of lithium metal, which can overcome the problem of lithium dendrites caused by uneven deposition of lithium ions and significantly improve the interface stability between the electrolyte and lithium metal.

[0007] Preferably, the polymer matrix is ​​a mixture of polyethylene glycol diacrylate (PEGDA) and polyvinylidene fluoride (PVDF), wherein PEGDA can form a cross-linked network through photoinitiated polymerization to orient the oriented nanorods, and the formed stable cross-linked network can also improve the mechanical strength of the electrolyte. The added PVDF has good film-forming properties and thermal stability, which can effectively improve the structural stability of the composite polymer electrolyte under high temperature conditions.

[0008] Preferably, the liquid electrolyte is composed of a lithium salt and an organic solvent; the lithium salt is at least one of lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium hexafluorophosphate, and lithium perchlorate; and the organic solvent is at least one of ethylene carbonate, dimethyl carbonate, 1,3-dioxolane, and ethylene glycol dimethyl ether. Nanorods with a hollow structure can store more liquid electrolyte, effectively prevent leakage of the electrolyte, and improve the electrochemical performance and safety performance of the composite polymer electrolyte.

[0009] According to a second aspect of the present invention, there is also provided a method for preparing the composite polymer electrolyte, comprising the following steps:

[0010] 1) Add anhydrous ferric chloride, concentrated hydrochloric acid and hexadecyltrimethylammonium bromide to water at 90 o C-120 o C, stirring for 10 h-20 h; after the stirring is completed, centrifuging, washing, and drying to obtain iron oxyhydroxide nanorods;

[0011] 2) adding the iron oxyhydroxide nanorods, urea, hexadecyltrimethylammonium bromide, isopropanol, cyclohexane and tetraethoxysilane obtained in step 1) into water, and reacting under reflux conditions; after the reaction is completed, cooling, centrifuging, washing and drying are performed to obtain SiO 2 coated iron oxyhydroxide nanorods;

[0012] 3) The SiO obtained in step 2) 2 The coated iron oxyhydroxide nanorods were calcined in air and hydrogen successively to obtain magnetic hollow nanorods;

[0013] 4) adding the magnetic hollow nanorods, polyethylene glycol diacrylate, polyvinylidene fluoride and photoinitiator obtained in step 3) to N-methylpyrrolidone, mixing them evenly, placing them in a magnetic field for vertical orientation, and irradiating them with ultraviolet light; curing the oriented magnetic hollow nanorods in a polymer matrix, and drying them to obtain a polymer electrolyte membrane;

[0014] 5) adding the polymer electrolyte membrane obtained in step 4) into a liquid electrolyte to obtain a composite polymer electrolyte containing magnetic hollow nanorods.

[0015] The present invention utilizes the magnetic field to make the magnetic Fe 3 O 4 @mSiO 2 The nanorods were vertically oriented and fixed by ultraviolet light-induced PEGDA polymerization to prepare a composite polymer electrolyte. 3 O 4 Nanorods are the core, with mesoporous SiO 2 There are no reports on the use of one-dimensional magnetic nanorods as nanofillers in composite polymer electrolytes, and the method of improving the electrochemical properties of the electrolyte by orienting the nanorods through an external magnetic field.

[0016] Preferably, in step 1), the mass ratio of hexadecyltrimethylammonium bromide, anhydrous ferric chloride, concentrated hydrochloric acid and water is 1:(7-9):(0.354-0.708):(80-100).

[0017] Preferably, in step 2), the mass ratio of iron oxyhydroxide nanorods, hexadecyltrimethylammonium bromide and tetraethoxysilane is 0.01:(0.5-0.8):(0.47-0.658).

[0018] Preferably, in step 2), the reflux condition is: the temperature is 60 o C-80 o C, time is 10 h-20 h. FeOOH@mSiO 2 The conditions for calcining the nanorods in air atmosphere are: calcination temperature is 400 o C-600 o C, calcination time is 2 h -4 h; calcination reduction conditions in hydrogen atmosphere are: calcination temperature is 200 o C-400 o C, calcination time is 3 h-8 h.

[0019] Preferably, in step 3), the mass ratio of the magnetic hollow nanorods, polyethylene glycol diacrylate, polyvinylidene fluoride, photoinitiator and N-methylpyrrolidone is (6-10): (40-60): (80-140): (10-20): (1000-3000). The photoinitiator is at least one of benzoin dimethyl ether, diphenyl acetone and 2-hydroxy-2-methylphenyl acetone.

[0020] Preferably, in step 4), the UV irradiation conditions are: distance 2 cm-5 cm, time 1 min-3 min. The irradiation time regulation can affect the polymerization reaction of the monomer. When the irradiation time is too short, the polymerization cannot be fully achieved; and when the irradiation time is too long, it will have a negative impact on the flexibility of the polymer.

[0021] According to the third aspect of the present invention, there is also provided the use of the composite polymer electrolyte containing the magnetic hollow nanorods in a lithium ion battery.

[0022] The beneficial effects of the present invention are as follows: the present invention utilizes the magnetic field to orient the magnetic Fe3O4@mSiO2 nanorods vertically, and fixes the nanorods by ultraviolet light-induced PEGDA polymerization, and the added PVDF can ensure the mechanical properties of the composite polymer electrolyte. On the one hand, the orderly arranged nanorods can form vertical lithium ion transmission channels, overcoming the problem of increasing the lithium ion conduction distance due to the irregular distribution of nanofillers, thereby obtaining higher ion conductivity; on the other hand, the orderly distributed hollow structure nanorods can provide more ion transmission channels, which can promote the uniform distribution of lithium ions on the lithium metal surface during the lithium deposition process, thereby improving the interface performance of lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Fe 3 O 4 @mSiO 2 Electron micrograph of nanorods;

[0024] Figure 2 Shown is the magnetic field orientation Fe 3 O 4 @mSiO 2 Scanning electron microscope images of the cross section of nanorods and unmagnetized nanorod gel electrolyte. ;

[0025] Figure 3 Shown are different magnetic field orientations and unmagnetized Fe 3 O 4 @mSiO 2 Ionic conductivity diagram of nanorod gel electrolyte;

[0026] Figure 4 The diagram shows the Fe2O3 arranged vertically on the vertical plane relative to the positive and negative electrodes and the Fe2O3 arranged horizontally on the vertical plane relative to the positive and negative electrodes. 3 O 4 @mSiO 2 Schematic diagram of the principle;

[0027] Figure 5 Fe 3 O 4 @mSiO 2 Cycling performance test diagram of lithium symmetric battery with vertical arrangement of nanorods in gel electrolyte;

[0028] Figure 6 Fe 3 O 4 @mSiO 2 Cycling performance test diagram of a battery with vertically arranged nanorods in a gel electrolyte. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments and drawings to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, scheme and effect of the present invention. It should be noted that the embodiments and features in the embodiments of this application can be combined with each other without conflict.

[0030] Example 1

[0031] A composite polymer electrolyte containing magnetic hollow nanorods, the preparation method of which comprises the following steps:

[0032] Anhydrous ferric chloride (7.77 g) was dissolved in 80 g water, and 0.531 g concentrated HCl (37%) and cetyltrimethylammonium bromide (CTAB, 1 g) were added. After mixing well, the mixture was heated at 98 o C for 16 hours. After the reaction solution was cooled, it was centrifuged and washed with water to obtain iron oxyhydroxide (FeOOH) nanorods.

[0033] Take out some iron oxyhydroxide (FeOOH) nanorods (0.01 g) and disperse them in water (15 g) for later use. Add urea (0.3 g), hexadecyltrimethylammonium bromide (CTAB, 0.5 g), isopropanol (1 mL), and cyclohexane (15 mL) to the FeOOH nanorod dispersion. After ultrasonic dispersion, add tetraethoxysilane (TEOS, 0.564 g) and 70 o C and refluxed for 16 hours. After cooling, centrifugation and washing, SiO 2 Coated iron oxyhydroxide nanorods (FeOOH@mSiO 2 ). 2 ) in air atmosphere 500 o C for 3 hours and then calcined in a hydrogen atmosphere at 300 o C for 4 hours to obtain Fe 3 O 4 @mSiO 2 Nanorods.

[0034] Ultrasonic treatment of Fe 3 O 4 @mSiO 2 (8.5 mg) was dispersed in 2 mL NMP, and PVDF (120 mg), PEGDA (50 mg, M n = 600), 2-hydroxy-2-methylpropiophenone photoinitiator (15 mg) to form a homogeneous solution. The solution was dropped on a glass slide and a magnetic field perpendicular to the ground was applied. At the same time, a UV lamp was irradiated at a distance of 2 cm from the glass for 1 minute to initiate PEGDA polymerization. The glass slide was placed in a vacuum drying oven and dried to remove the solvent to obtain a polymer electrolyte membrane. The electrolyte membrane was immersed in a 1M LiTFSI (DOL : DME = v : v =1 : 1) electrolyte to obtain a composite polymer electrolyte (VA-CPE).

[0035] Figure 1 Fe 3 O 4 @mSiO 2 The nanorod morphology shows a capsule morphology. Figure 2 a is Fe 3 O 4 @mSiO 2 Electron micrograph of nanorods vertically aligned in a gel electrolyte. Figure 3 is the conductivity of nanorods with different arrangement directions in the gel electrolyte. It can be seen that the vertically arranged nanorods (VA-CPE) have the highest ionic conductivity. Figure 4 Schematic diagram of uniform lithium-ion channels of vertically aligned nanorods. Figure 5 This is a test chart of the cycling performance of a lithium-to-lithium battery with a vertically arranged nanorod electrolyte. It can be seen that its cycle life is greater than 3000 hours and the voltage distribution is stable. There is no internal short circuit caused by the formation of lithium dendrites during the cycle. Figure 6 This is a test chart of the cycle performance of a battery with vertically arranged nanorod electrolyte. It is charged and discharged at 0.5 C, and its capacity retention rate remains 70% after 500 cycles.

[0036] Example 2

[0037] A composite polymer electrolyte containing magnetic hollow nanorods, the preparation method of which comprises the following steps:

[0038] Anhydrous ferric chloride (7 g) was dissolved in 80 g water, and 0.354 g concentrated HCl (37%) and cetyltrimethylammonium bromide (CTAB, 1 g) were added. After mixing well, the mixture was heated at 90 o C for 15 hours. After the reaction solution was cooled, it was centrifuged and washed with water to obtain iron oxyhydroxide (FeOOH) nanorods.

[0039] Take out some iron oxyhydroxide (FeOOH) nanorods (0.01 g) and disperse them in water (15 g) for later use. Add urea (0.3 g), hexadecyltrimethylammonium bromide (CTAB, 0.3 g), isopropanol (1 mL), and cyclohexane (15 mL) to the FeOOH nanorod dispersion. After ultrasonic dispersion, add tetraethoxysilane (TEOS, 0.47 g) and 70 o C and refluxed for 15 hours. After cooling, centrifugation and washing, SiO 2 Coated iron oxyhydroxide nanorods (FeOOH@mSiO 2 ). 2 ) in air atmosphere 500 o C for 3 hours and then calcined in a hydrogen atmosphere at 300 o C for 4 hours to obtain Fe 3 O 4 @mSiO 2 Nanorods.

[0040] Ultrasonic wave was used to transfer Fe3O4@mSiO 2 (6 mg) was dispersed in 1 mL NMP, and PVDF (80 mg), PEGDA (40 mg, M n=600), benzoin dimethyl ether (10 mg), form a homogeneous solution, drop the solution on a glass slide, and apply a magnetic field perpendicular to the ground. At the same time, a UV lamp is irradiated at a distance of 5 cm from the glass for 3 minutes to initiate PEGDA polymerization. The glass slide is placed in a vacuum drying oven, and the solvent is dried to obtain a polymer electrolyte membrane. The electrolyte membrane is immersed in a 1M LiTFSI (DOL: DME = v: v =1: 1) electrolyte to obtain a composite polymer electrolyte.

[0041] Example 3

[0042] A composite polymer electrolyte containing magnetic hollow nanorods, the preparation method of which comprises the following steps:

[0043] Anhydrous ferric chloride (8 g) was dissolved in 90 g water, and 0.472 g concentrated HCl (37%) and cetyltrimethylammonium bromide (CTAB, 1 g) were added. After mixing well, the mixture was heated at 90 o C for 20 hours. After the reaction solution was cooled, it was centrifuged and washed with water to obtain iron oxyhydroxide (FeOOH) nanorods.

[0044] Take out some iron oxyhydroxide (FeOOH) nanorods (0.01 g) and disperse them in water (15 g) for later use. Add urea (0.3 g), hexadecyltrimethylammonium bromide (CTAB, 0.4 g), isopropanol (1 mL), and cyclohexane (15 mL) to the FeOOH nanorod dispersion. After ultrasonic dispersion, add tetraethoxysilane (TEOS, 0.564 g) and 60 o C and refluxed for 20 hours. After cooling, centrifugation and washing, SiO 2 Coated iron oxyhydroxide nanorods (FeOOH@mSiO 2 ). 2 ) in air atmosphere 400 o C for 4 hours and then in a hydrogen atmosphere at 200 o C for 8 hours to obtain Fe 3 O 4 @mSiO 2 Nanorods.

[0045] Ultrasonic treatment of Fe 3 O 4 @mSiO 2 (8 mg) was dispersed in 2 mL NMP, and PVDF (100 mg), PEGDA (50 mg, M n=600), diphenylacetophenone photoinitiator (15 mg), form a homogeneous solution, drop the solution on a glass slide, and apply a magnetic field perpendicular to the ground. At the same time, a UV lamp is irradiated at a distance of 3 cm from the glass for 2 minutes to initiate PEGDA polymerization. The glass slide is placed in a vacuum drying oven, and the solvent is dried to obtain a polymer electrolyte membrane. The electrolyte membrane is immersed in a 1M LiFSI (DOL : DME = v : v =1 : 1) electrolyte to obtain a composite polymer electrolyte.

[0046] Example 4

[0047] A composite polymer electrolyte containing magnetic hollow nanorods, the preparation method of which comprises the following steps:

[0048] Anhydrous ferric chloride (9 g) was dissolved in 100 g water, and 0.708 g concentrated HCl (37%) and cetyltrimethylammonium bromide (CTAB, 1 g) were added. After mixing well, the mixture was heated at 120 o C for 10 hours. After the reaction solution was cooled, it was centrifuged and washed with water to obtain iron oxyhydroxide (FeOOH) nanorods.

[0049] Take out some iron oxyhydroxide (FeOOH) nanorods (0.01 g) and disperse them in water (15 g) for later use. Add urea (0.3 g), hexadecyltrimethylammonium bromide (CTAB, 0.5 g), isopropanol (1 mL), and cyclohexane (15 mL) to the FeOOH nanorod dispersion. After ultrasonic dispersion, add tetraethoxysilane (TEOS, 0.658 g) and 80 o C and refluxed for 10 hours. After cooling, centrifugation and washing, SiO 2 Coated iron oxyhydroxide nanorods (FeOOH@mSiO 2 ). 2 ) in air atmosphere 600 o C for 2 hours and then calcined in a hydrogen atmosphere at 400 o C for 3 hours to obtain Fe 3 O 4 @mSiO 2 Nanorods.

[0050] Ultrasonic treatment of Fe 3 O 4 @mSiO 2 (10 mg) was dispersed in 3 mL NMP, and PVDF (140 mg), PEGDA (60 mg, M n=600), diphenylacetophenone photoinitiator (20 mg), form a homogeneous solution, drop the solution on a glass slide, and apply a magnetic field perpendicular to the ground. At the same time, a UV lamp is irradiated at a distance of 5 cm from the glass for 3 minutes to initiate PEGDA polymerization. The glass slide is placed in a vacuum drying oven and dried to remove the solvent to obtain a polymer electrolyte membrane. The electrolyte membrane is soaked in 1M LiPF 6 (DOL : DME = v : v =1 : 1) electrolyte to obtain a composite polymer electrolyte.

[0051] Example 5

[0052] A composite polymer electrolyte containing magnetic hollow nanorods, the preparation method of which comprises the following steps:

[0053] Anhydrous ferric chloride (9 g) was dissolved in 100 g water, and 0.708 g concentrated HCl (37%) and cetyltrimethylammonium bromide (CTAB, 1 g) were added. After mixing well, the mixture was heated at 110 o C for 18 hours. After the reaction solution was cooled, it was centrifuged and washed with water to obtain iron oxyhydroxide (FeOOH) nanorods.

[0054] Take out some iron oxyhydroxide (FeOOH) nanorods (0.01 g) and disperse them in water (15 g) for later use. Add urea (0.3 g), hexadecyltrimethylammonium bromide (CTAB, 0.6 g), isopropanol (1 mL), and cyclohexane (15 mL) to the FeOOH nanorod dispersion. After ultrasonic dispersion, add tetraethoxysilane (TEOS, 0.658 g), 65 o C and refluxed for 18 hours. After cooling, centrifugation and washing, SiO 2 Coated iron oxyhydroxide nanorods (FeOOH@mSiO 2 ). 2 ) in air atmosphere 500 o C for 3 hours and then calcined in a hydrogen atmosphere at 300 o C for 5 hours to obtain Fe 3 O 4 @mSiO 2 Nanorods.

[0055] Ultrasonic treatment of Fe 3 O 4 @mSiO 2 (8.5 mg) was dispersed in 3 mL NMP, and PVDF (120 mg), PEGDA (50 mg, M n= 600), 2-hydroxy-2-methylpropiophenone photoinitiator (15 mg), to form a homogeneous solution. The solution was dropped on a glass slide and a magnetic field perpendicular to the ground was applied. At the same time, a UV lamp was irradiated at a distance of 4 cm from the glass for 2 minutes to initiate PEGDA polymerization. The glass slide was placed in a vacuum drying oven and dried to remove the solvent to obtain a polymer electrolyte membrane. The electrolyte membrane was soaked in 1M LiClO 4 (EC : DMC = v : v =1 : 1) electrolyte to obtain a composite polymer electrolyte.

[0056] Example 6

[0057] A composite polymer electrolyte containing magnetic hollow nanorods, the preparation method of which comprises the following steps:

[0058] Anhydrous ferric chloride (7.77 g) was dissolved in 80 g water, and 0.531 g concentrated HCl (37%) and cetyltrimethylammonium bromide (CTAB, 1 g) were added. After mixing well, the mixture was heated at 98 o C for 16 hours. After the reaction solution was cooled, it was centrifuged and washed with water to obtain iron oxyhydroxide (FeOOH) nanorods.

[0059] Take out some iron oxyhydroxide (FeOOH) nanorods (0.01 g) and disperse them in water (15 g) for later use. Add urea (0.3 g), hexadecyltrimethylammonium bromide (CTAB, 0.5 g), isopropanol (1 mL), and cyclohexane (15 mL) to the FeOOH nanorod dispersion. After ultrasonic dispersion, add tetraethoxysilane (TEOS, 0.564 g), 65 o C and refluxed for 18 hours. After cooling, centrifugation and washing, SiO 2 Coated iron oxyhydroxide nanorods (FeOOH@mSiO 2 ). 2 ) in air atmosphere 450 o C for 3.5 hours and then calcined in a hydrogen atmosphere at 350 o C for 5.5 hours to obtain Fe 3 O 4 @mSiO 2 Nanorods.

[0060] Ultrasonic treatment of Fe 3 O 4 @mSiO 2 (7 mg) was dispersed in 2 mL NMP, and PVDF (100 mg), PEGDA (50 mg, M n= 600), 2-hydroxy-2-methylpropiophenone photoinitiator (15 mg) to form a homogeneous solution. The solution was dropped on a glass slide and a magnetic field perpendicular to the ground was applied. At the same time, a UV lamp was irradiated at a distance of 2 cm from the glass for 1 minute to initiate PEGDA polymerization. The glass slide was placed in a vacuum drying oven and dried to remove the solvent to obtain a polymer electrolyte membrane. The electrolyte membrane was immersed in a 1M LiTFSI (DOL : DME = v : v =1 : 1) electrolyte to obtain a composite polymer electrolyte.

[0061] Example 7

[0062] A composite polymer electrolyte containing magnetic hollow nanorods, the preparation method of which comprises the following steps:

[0063] Anhydrous ferric chloride (7.77 g) was dissolved in 80 g water, and 0.531 g concentrated HCl (37%) and cetyltrimethylammonium bromide (CTAB, 1 g) were added. After mixing well, the mixture was heated at 100 o C for 12 hours. After the reaction solution was cooled, it was centrifuged and washed with water to obtain iron oxyhydroxide (FeOOH) nanorods.

[0064] Take out some iron oxyhydroxide (FeOOH) nanorods (0.01 g) and disperse them in water (15 g) for later use. Add urea (0.3 g), hexadecyltrimethylammonium bromide (CTAB, 0.5 g), isopropanol (1 mL), and cyclohexane (15 mL) to the FeOOH nanorod dispersion. After ultrasonic dispersion, add tetraethoxysilane (TEOS, 0.564 g) and 75 o C and refluxed for 12 hours. After cooling, centrifugation and washing, SiO 2 Coated iron oxyhydroxide nanorods (FeOOH@mSiO 2 ). 2 ) in air atmosphere 550 o C for 2.5 hours and then calcined in a hydrogen atmosphere at 320 o C for 4.5 hours to obtain Fe 3 O 4 @mSiO 2 Nanorods.

[0065] Ultrasonic treatment of Fe 3 O 4 @mSiO 2 (7 mg) was dispersed in 2 mL NMP, and PVDF (100 mg), PEGDA (50 mg, M n= 600), benzoin dimethyl ether photoinitiator (15 mg), to form a homogeneous solution. The solution was dropped on a glass slide and a magnetic field perpendicular to the ground was applied. At the same time, a UV lamp was irradiated at a distance of 2 cm from the glass for 1 minute to initiate PEGDA polymerization. The glass slide was placed in a vacuum drying oven and dried to remove the solvent to obtain a polymer electrolyte membrane. The electrolyte membrane was soaked in 1M LiPF 6 (DOL : DME = v : v =1 : 1) electrolyte to obtain a composite polymer electrolyte.

[0066] Comparative Example 1

[0067] A composite polymer electrolyte (HA-CPE), the preparation method of which comprises the following steps (compared with Example 1, this embodiment applies a magnetic field parallel to the ground):

[0068] Anhydrous ferric chloride (7.77 g) was dissolved in 80 g water, and 0.531 g concentrated HCl (37%) and cetyltrimethylammonium bromide (CTAB, 1 g) were added. After mixing well, the mixture was heated at 98 o C for 16 hours. After the reaction solution was cooled, it was centrifuged and washed with water to obtain iron oxyhydroxide (FeOOH) nanorods.

[0069] Take out some iron oxyhydroxide (FeOOH) nanorods (0.01 g) and disperse them in water (15 g) for later use. Add urea (0.3 g), hexadecyltrimethylammonium bromide (CTAB, 0.5 g), isopropanol (1 mL), and cyclohexane (15 mL) to the FeOOH nanorod dispersion. After ultrasonic dispersion, add tetraethoxysilane (TEOS, 0.564 g) and 70 o C and refluxed for 16 hours. After cooling, centrifugation and washing, SiO 2 Coated iron oxyhydroxide nanorods (FeOOH@mSiO 2 ). 2 ) in air atmosphere 500 o C for 3 hours and then calcined in a hydrogen atmosphere at 300 o C for 4 hours to obtain Fe 3 O 4 @mSiO 2 Nanorods.

[0070] Ultrasonic treatment of Fe 3 O 4 @mSiO 2 (8.5 mg) was dispersed in 3 mL NMP, and PVDF (120 mg), PEGDA (50 mg, M n=600), 2-hydroxy-2-methylpropiophenone photoinitiator (15 mg), to form a homogeneous solution, the solution was dropped on a glass slide, and a magnetic field parallel to the ground was applied. At the same time, a UV lamp was irradiated at a distance of 2 cm from the glass for 1 minute to initiate PEGDA polymerization. The glass slide was placed in a vacuum drying oven, and the solvent was dried to obtain a polymer electrolyte membrane. The electrolyte membrane was immersed in a 1M LiTFSI (DOL : DME = v : v =1:1) electrolyte to obtain a composite polymer electrolyte (HA-CPE).

[0071] Figure 2 b is Fe 3 O 4 @mSiO 2 Electron micrograph of nanorods arranged laterally in a gel electrolyte. Figure 3 It can be seen that the laterally aligned nanorods (HA-CPE) have the lowest ionic conductivity. Figure 4 Schematic diagram of uniform lithium-ion channels of laterally arranged nanorods.

[0072] Comparative Example 2

[0073] A composite polymer electrolyte (RA-CPE), the preparation method of which comprises the following steps (compared with Example 1, this embodiment does not apply any magnetic field):

[0074] Anhydrous ferric chloride (7.77 g) was dissolved in 80 g water, and 0.531 g concentrated HCl (37%) and cetyltrimethylammonium bromide (CTAB, 1 g) were added. After mixing well, the mixture was heated at 98 o C for 16 hours. After the reaction solution was cooled, it was centrifuged and washed with water to obtain iron oxyhydroxide (FeOOH) nanorods.

[0075] Take out some iron oxyhydroxide (FeOOH) nanorods (0.01 g) and disperse them in water (15 g) for later use. Add urea (0.3 g), hexadecyltrimethylammonium bromide (CTAB, 0.5 g), isopropanol (1 mL), and cyclohexane (15 mL) to the FeOOH nanorod dispersion. After ultrasonic dispersion, add tetraethoxysilane (TEOS, 0.564 g) and 70 o C and refluxed for 16 hours. After cooling, centrifugation and washing, SiO 2 Coated iron oxyhydroxide nanorods (FeOOH@mSiO 2 ). 2 ) in air atmosphere 500 o C for 3 hours and then calcined in a hydrogen atmosphere at 300 o C for 4 hours to obtain Fe 3 O4 @mSiO 2 Nanorods.

[0076] Ultrasonic treatment of Fe 3 O 4 @mSiO 2 (8.5 mg) was dispersed in 2 mL NMP, and PVDF (120 mg), PEGDA (50 mg, M n =600), 2-hydroxy-2-methylpropiophenone photoinitiator (15 mg), to form a homogeneous solution, the solution was dropped on a glass slide without applying any magnetic field. At the same time, a UV lamp was irradiated at a distance of 2 cm from the glass for 1 minute to initiate PEGDA polymerization. The glass slide was placed in a vacuum drying oven, and the solvent was dried to obtain a polymer electrolyte membrane. The electrolyte membrane was immersed in a 1M LiTFSI (DOL :DME = v : v =1 : 1) electrolyte to obtain a composite polymer electrolyte (RA-CPE).

[0077] Figure 2 c is Fe 3 O 4 @mSiO 2 Electron micrograph of disordered arrangement of nanorods in gel electrolyte. Figure 3 It can be seen that the ionic conductivity of the disordered nanorods (RA-CPE) is in the middle. This is because the nanorods without a magnetic field still have fewer lithium ion channels in the vertical direction than the vertical nanorods, so the conductivity is in the middle.

[0078] In summary, the composite polymer electrolyte prepared in the present invention, wherein the magnetic hollow nanorods play an important role in the mechanical strength and electrochemical properties of the composite polymer electrolyte. 3 O 4 The core is introduced into the filler. Applying a magnetic field to the electrolyte during the preparation of the polymer electrolyte can induce the nanorods to form vertically oriented ion transmission channels, overcoming the problem of increased lithium ion conduction distance due to irregular distribution of nanofillers, thereby obtaining higher ion conductivity; and in the lithium deposition process, the orderly distributed ion transmission channels can promote the uniform distribution of lithium ions on the surface of lithium metal, which can overcome the problem of lithium dendrites caused by uneven deposition of lithium ions and significantly improve the interface stability between the electrolyte and lithium metal.

[0079] The above is only a preferred embodiment of the present invention. The present invention is not limited to the above implementation. As long as the technical effect of the present invention is achieved by the same means, it should belong to the protection scope of the present invention. Within the protection scope of the present invention, its technical scheme and / or implementation method can have various modifications and changes.

Claims

1. A composite polymer electrolyte containing magnetic hollow nanorods, characterized in that: The composite polymer electrolyte comprises a magnetic hollow nanorod, a polymer matrix and a liquid electrolyte; the magnetic hollow nanorod is a nanofiller of SiO2 coated with magnetic Fe3O4; the polymer matrix is ​​a mixture of polyethylene glycol diacrylate and polyvinylidene fluoride; the preparation method of the composite polymer electrolyte comprises the following steps: 1) adding anhydrous ferric chloride, concentrated hydrochloric acid and hexadecyltrimethylammonium bromide to water, stirring at 90°C-120°C for 10h-20h; after the reaction is completed, centrifuging, washing and drying to obtain iron oxyhydroxide nanorods; 2) adding the iron oxyhydroxide nanorods, urea, hexadecyltrimethylammonium bromide, isopropanol, cyclohexane and tetraethoxysilane obtained in step 1) to water, and reacting under reflux conditions; after the reaction is completed, cooling, centrifuging, washing and drying to obtain SiO2-coated iron oxyhydroxide nanorods; 3) calcining the SiO2-coated iron oxyhydroxide nanorods obtained in step 2) in air and hydrogen in turn to obtain magnetic hollow nanorods; 4) adding the magnetic hollow nanorods, polyethylene glycol diacrylate, polyvinylidene fluoride and photoinitiator obtained in step 3) to N-methylpyrrolidone, mixing them evenly, placing them in a magnetic field for vertical orientation, and irradiating them with ultraviolet light; curing the oriented magnetic hollow nanorods in a polymer matrix, and drying them to obtain a polymer electrolyte membrane; 5) adding the polymer electrolyte membrane obtained in step 4) into a liquid electrolyte to obtain the composite polymer electrolyte containing the magnetic hollow nanorods.

2. The composite polymer electrolyte according to claim 1, characterized in that The liquid electrolyte consists of a lithium salt and an organic solvent; the lithium salt is at least one of lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium hexafluorophosphate, and lithium perchlorate; and the organic solvent is at least one of ethylene carbonate, dimethyl carbonate, 1,3-dioxolane, and ethylene glycol dimethyl ether.

3. The composite polymer electrolyte according to claim 1, characterized in that In the step 1), the mass ratio of the hexadecyltrimethylammonium bromide, the anhydrous ferric chloride, the concentrated hydrochloric acid and the water is 1:(7-9):(0.354-0.708):(80-100).

4. The composite polymer electrolyte according to claim 1, characterized in that In the step 2), the mass ratio of the iron oxyhydroxide nanorods, the hexadecyltrimethylammonium bromide and the tetraethoxysilane is 0.01:(0.5-0.8):(0.47-0.658).

5. The composite polymer electrolyte according to claim 1, characterized in that In the step 2), the reflux conditions are: temperature of 60° C.-80° C., and time of 10 h-20 h.

6. The composite polymer electrolyte according to claim 1, characterized in that In the step 3), the mass ratio of the magnetic hollow nanorods, the polyethylene glycol diacrylate, the polyvinylidene fluoride, the photoinitiator and the N-methylpyrrolidone is (6-10): (40-60): (80-140): (10-20): (1000-3000).

7. The composite polymer electrolyte according to claim 1, characterized in that In the step 4), the irradiation conditions of the ultraviolet light are: a distance of 2 cm-5 cm and a time of 1 min-3 min.

8. Use of the composite polymer electrolyte containing magnetic hollow nanorods according to claim 1 in lithium ion batteries.

Citation Information

Patent Citations

  • Highly ordered lithium battery block polymer electrolyte membrane and preparation method thereof

    CN112421122A